Implementasi Metode Ummi Dalam Pembelajaran Al-Quran Di Mi Integral Al-Ukhuwwah Banjang - Raihanah Raihanah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
This study aims to understand, analyze, and describe the Ummi method developed at MI Integral Al-Ukhuwwah Banjang, namely the implementation of the Ummi method at MI Integral Al-Ukhuwwah and the quality of Al-Quran reading after the Ummi method was applied. This research uses a qualitative descriptive method with a case study type. This research data source is divided into two, namely primary data sources and secondary data. Using observation data collection instruments, interviews, and documentation. Research informants namely the Principal, Ummi Coordinator, and Students. The application of learning the Koran using the Ummi method has had a very good impact on improving the quality of reading the Koran at MI Integral Al-Ukhuwwah Banjang.